REKONSTRUKSI KEDUDUKAN KETETAPAN MAJELIS PERMUSYAWARATAN RAKYAT DALAM HIERARKI PERATURAN PERUNDANG-UNDANGAN - HAERUMAN JAYADI; AD. BASNIWATI; LALU GUNA NUGRAHA (GANEC SWARA, 2022)
The purpose of this study was to determine the position of the Decree of the People's Consultative Assembly based on the science/theory of legislation with a specific target in the form of producing teaching materials in the subjects of Constitutional Law and Legislation. The research method used is a normative legal research method using a statutory approach and a conceptual approach. Based on the research, it was found that the MPR Decree which is still in effect today is the MPR Decree which is regulatory in nature while the MPR Decree which is stipulating/decision is no longer in effect. Various legal issues arise from the existence of the MPR tap which is placed in a higher position/level in on the Law, which is related to the testing, namely the tools/testing stones and the authorized institution to test it. The ideal position in the future if you still want to maintain the existence and enforceability of the MPR Decree is to place the MPR Decree on an equal footing with the Law. The suggestions that can be given based on the results of the research and discussion as well as the conclusions mentioned above are as follows: The legislators, in this case the DPR and the President, shall immediately form a law which regulates the contents of the MPR Decree which is still valid. The legislators revise or amend Law no. 12 of 2011 concerning UUUP3 Article 7 paragraph (1) by placing the MPR Decree as equal to the Law.